Significance of management commitment & participation, and employee training & empowerment on marketing performance of Kuehne+Nagel Ltd Bangladesh - Rahman, Md. Arafat (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.